2001
DOI: 10.1038/nbt0901-870
|View full text |Cite
|
Sign up to set email alerts
|

Stable genetic transformation of tomato plastids and expression of a foreign protein in fruit

Abstract: Transgenic chloroplasts offer unique advantages in plant biotechnology, including high-level foreign protein expression, absence of epigenetic effects, and gene containment due to the lack of transgene transmission through pollen. However, broad application of plastid genome engineering in biotechnology has been largely hampered by both the lack of chloroplast transformation systems for major crop plants and the usually low plastid gene expression levels in nongreen tissues such as fruits, tubers, and other st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
336
0
12

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(361 citation statements)
references
References 34 publications
9
336
0
12
Order By: Relevance
“…The transformation frequency of 1.5×10 −6 is around tenfold lower than that reported for Nicotiana in similar protoplast/plastid transformation studies with vectors containing binding-type markers (Kavanagh et al 1999) or aadA as a dominant antibiotic resistance marker (Kofer et al 1998). Ruf et al (2001) reported successful tomato plastid transformation using the biolistic method for DNA delivery into leaf discs with selection based on the introduced aadA resistance gene. These authors also found that the transformation frequency in tomato was lower than that obtainable with tobacco.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The transformation frequency of 1.5×10 −6 is around tenfold lower than that reported for Nicotiana in similar protoplast/plastid transformation studies with vectors containing binding-type markers (Kavanagh et al 1999) or aadA as a dominant antibiotic resistance marker (Kofer et al 1998). Ruf et al (2001) reported successful tomato plastid transformation using the biolistic method for DNA delivery into leaf discs with selection based on the introduced aadA resistance gene. These authors also found that the transformation frequency in tomato was lower than that obtainable with tobacco.…”
Section: Discussionmentioning
confidence: 82%
“…Plastid transformation of tobacco (Nicotiana tabacum) is routine in a number of laboratories, but there are only a limited number of isolated reports relating to genera outside Nicotiana. These include tomato (Ruf et al 2001), rice (Khan and Maliga 1999), potato (Sidorov et al 1999), carrot (Kumar et al 2004) and several Brassicaceae, including Arabidopsis (Sikdar et al 1998), Brassica napus (Hou et al 2002) and Lesquerella fendleri (Skarjinskaia et al 2003). All of these investigators used biolistics to deliver DNA into chloroplasts.…”
Section: Introductionmentioning
confidence: 99%
“…The pZF7lox plastid transformation vectors are derived from plasmids pZSJH1 (Birch-Machin et al 2004) and pRB95 (Ruf et al 2001). The plastoglobulin35 (PGL35)-ORF without the coding sequence for the transit peptide gene was amplified from pCL61-PGL35 with PGL35-F forward primer introducing a NcoI restriction site at the 5 0 -end and with PGL35-R reverse primer introducing the coding sequence for three TEV protease sites as well as NdeI and XbaI restriction sites at the 3 0 end.…”
Section: Cloning Proceduresmentioning
confidence: 99%
“…In transplastomic tomato plants, the fusion protein P24-Nef from HIV accumulated up to 40% TSP in leaves, but significantly less in green and ripe fruits (2.5% and nil, respectively) (Zhou et al 2008). The relative expression level of transgenes in tomato fruit chromoplasts, however, was higher with other proteins (Ruf et al 2001) and in any case sufficient to induce significant metabolic changes (Wurbs et al 2007;Apel and Bock 2009). Very low levels of mRNA and GFP protein were detected in roots of transplastomic Nicotiana benthamiana plants (less than 2% of that in the leaves), albeit expression levels up to 40-75% of those in leaf chloroplasts could be achieved in petal leucoplasts of the same plants or in chromoplasts of carrot taproots (Kumar et al 2004a;Davarpanah et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, however, low transformation efficiencies have been reported for species other than tobacco (Sikdar et al 1998;Sidorov et al 1999;Ruf et al 2001;Hou et al 2003;Skarjinskaia et al 2003;Zubko et al 2004;Nguyen et al 2005;Nugent et al 2006;De Marchis et al 2009). Low recovery of transplastomic shoots has been attributed to multiple reasons, such as a relatively inefficient homologous recombination system, non-optimal homology and length of flanking regions, the promoter used for the expression of the selectable marker gene, the kind of explant, or the regeneration protocol.…”
Section: Introductionmentioning
confidence: 99%